THE STRATEGIC ASPECTS AND RESULTS OF AGRICULTURE DEVELOPMENT IN SERBIA IN THE TRANSITION PERIOD - Aničić, Jugoslav; Vukotić, Svetlana; Krstić, Svetozar (Economics of Agriculture, 2016)
The economic development in Yugoslavia (Serbia) after the second world war has been conducted at the expense of agriculture because the industrialisation was in the forefront of the economic policy. It has an impact on the present position of the agriculture compared to the other sectors because the parity of product exchange is still retained at the expense of agriculture. Even under these circumstances agriculture is an industry with a positive foreign trade balance, important share in the national product and the unemployment rate reduction, and that has been analysed and shown in this paper. Many developed European countries are an example of the successful agricultural development as a carrier of the complete development. There are indisputably much wider possibilities for agriculture development in Serbia, and it could become a great comparative advantage of our economy in the developed markets in the world, with the appropriate macroeconomic policy.